An Examination of the Relationship Between Emotion Regulation and Psychological Recovery in Sports - Tastan, Zarife (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
This study aims to examine the predictive role of athletes’ emotion regulation strategies, specifically cognitive reappraisal and suppression, on psychological recovery. The high emotional intensity and stress inherent in sports environments increase the importance of emotion regulation skills for athlete health and psychological recovery. The research was conducted using a correlational research design, with data collected from 408 licensed athletes aged 17-25 who actively engage in sports in Istanbul. Participants were selected through criterion sampling, a type of purposive sampling method. Data were gathered using the Emotion Regulation Scale for Athletes and Sport Psychological Recovery Scale. Independent samples t-tests, one-way analysis of variance (ANOVA), and multiple linear regression analyses were applied to the data. Findings revealed that cognitive reappraisal significantly and positively predicted psychological recovery, whereas suppression negatively predicted it. Significant differences in psychological recovery levels were found with respect to certain demographic variables such as gender, type of sport, and years of sports experience, while no significant differences were observed for emotional strain and psychological support variables. These results highlight the critical role of emotion regulation strategies in athlete health and well-being.